PERANCANGAN TACTILE BOOK SEBAGAI MEDIA PEMBELAJARAN AKSARA SUNDA UNTUK TUNANETRA - Darmawan, Agus; Desmiati, Putri (Universitas Mercu Buana, 2024)
Indonesia has various kinds of culture that we can see such as traditional clothing, rare ancient objects, music, dance, etc. One of the many Indonesian cultures in West Java is the Sundanese script. Sundanese script is also a social component that is maintained, including for the younger generation with special needs such as the blind. article 6 section 6 Republic of Indonesia Regulation no. 4 of 1997 concerning Persons with Disabilities, specifically explains that every person with disabilities has the same freedom to develop their talents, potential and community activities, especially for the younger generation of people with disabilities in the family and local environment. This research aims to develop Sundanese script for the blind using Tactile book media. Tactile books are books that have visual illustrations that can be read with the sense of touch. The method applied in this research is a qualitative descriptive method with data collection methods through literature studies and interviews. Results of exploration through planning material books as a vehicle for learning Sundanese script for the blind. The aim of the results of this research is to provide useful information for blind people in order to preserve Sundanese script culture in Sukabumi.